Effect of Activated Charcoal on Bovine Enamel Shade/ Karen Joy A. Donila and Kathleen Marie A. Ferrer. - Donila, Karen Joy A.
INTRODUCTION: People try to improve their smile by having whiter teeth. While there is an obvious demand for teeth whitening products and services, not everyone can afford them. As a result, people may resort to Do it Yourself versions of these practices because they are cheaper alternatives to teeth whitening. The one gaining internet popularity is whitening teeth using activated charcoal.